Film collection: The Shame (Journal of Parents and Teachers, 2012)
The shame is  a film that takes place in a morning in the life of Pepe and Lucía, a couple of forty years old, moderns and accommodated in Madrid, that decides to tell Jimena, a social worker, that life with Manu, a eight-year-old peruavian son that is living with them, it is very difficult. They tell Jimena that the last six months that they have spent with Manu have been hell. This is the reason why they want to return the child. However, a decisition like this requires some thinking because this kind of decisition arise problems and personal issues in the couple if they want to go on with the process.
Keywords: Affectivity and Feeling; Behaviour; Family environment; Personality development.; cinema and education